The Role of the Sensory Stimuli in Building Consumer Satisfaction Using Services - Taranko , Teresa (Studia Oeconomica Posnaniensia, 2018)
The subject of the paper is the role of the sensory stimuli in shaping consumer experience and their satisfaction with the use of services, in particular food and beauty services. In addition to theoretical considerations the results of their own research among consumers using the services of selected restaurant and beauty salon are presented. The subject of the study was subjectively perceived by consumers, the role of the various incentives in the delivery and assessment of the quality of the services and amenities by the prism of sensory experience.